Urban Farming Towards Enhancing Food Security in Highly Urbanized Cities in the Philippines, A Community Sustainability Response - Areola, PhD HSG, Eunice Mareth Querol; Dacones, Dacones Galit (Sekolah Tinggi Manajemen IPMI, 2024)
Using comparative data, this study looked at small and medium-scale farming in highly urbanized cities in the Philippines, including community gardens, rooftop farms, and backyard gardens, excluding rural-like or peri-urban farming practices that focus on food production. It highlights the effects on food insecurity, daily spending, and environmental sustainability at the household level without performing life-cycle analysis of agricultural systems. The short-term and local effects of urban farming that looks into the selected cities' social and economic difficulties, and the area's sustainability were highlighted in this study.